Johann Gaspar Spurzheim: A Life Dedicated to Phrenology - Bilal, Mohammad (Cureus, 2017)
Loved for his empathetic nature but admired for his analytical mind, Gaspar Spurzheim (1776-1832) was a prominent contributor to phrenology, a field of neuroscience focused on studying the shapes of the skulls in relation to the activity levels of certain functional areas of the brain. This curiosity about the connection between physical characteristics and brain function was seeded in the young mind of Spurzheim when he observed that classmates with seemingly superb memories also appeared to have bright eyes. It launched Spurzheim on a journey to study the shape and function of the brain, which eventually led him to his mentor Franz Gall. Together, they classified many functional areas of the brain while touring Europe, describing their findings to audiences that filled lecture theaters to the brim. During their lectures, Gall focused on explaining findings while Spurzheim focused on dissections and demonstrations. After spending significant time with his mentor, captivating audiences and spreading the ideas of phrenology through several books and journal publications, Spurzheim left their fruitful partnership and started lecturing on his own. He toured the UK, giving lectures and dissections in London and Edinburgh, gaining universal respect for his dissection methods, writing several books and publishing articles in what were then major journals. With the aid of his wife’s artistic skills in painting and sketching many of dissections, Spurzheim’s popularity extended beyond the phrenological community. It eventually led him to Boston, where he opened this field of science in America before his death in 1832. Although phrenology has lost its popularity, Spurzheim’s contributions to our anatomical understanding of the brain survive.